Prospective comparison of real‐time tissue elastography and serum fibrosis markers for the estimation of liver fibrosis in chronic hepatitis C patients. Issue 7 (10th July 2013) - Tamaki, Nobuharu; Kurosaki, Masayuki; Matsuda, Shuya; Nakata, Toru; Muraoka, Masaru; Suzuki, Yuichiro; Yasui, Yutaka; Suzuki, Shoko; Hosokawa, Takanori; Nishimura, Takashi; Ueda, Ken; Tsuchiya, Kaoru; et al.
<x xml:space="preserve">Abstract</x> Aim Real‐time tissue elastography (RTE) is a non‐invasive method for the measurement of tissue elasticity using ultrasonography. Liver fibrosis (LF) index is a quantitative method for evaluation of liver fibrosis calculated by RTE image features. This study aimed to investigate the significance of LF index for predicting liver fibrosis in chronic hepatitis C patients. Methods In this prospective study, 115 patients with chronic hepatitis C who underwent liver biopsy were included, and the diagnostic accuracy of LF index and serum fibrosis markers was evaluated. Results RTE imaging was successfully performed on all patients. Median LF index in patients with F0–1, F2, F3 and F4 were 2.61, 3.07, 3.54 and 4.25, respectively, demonstrating a stepwise increase with liver fibrosis progression (P < 0.001). LF index (odds ratio [OR] = 5.3, 95% confidence interval [CI] = 2.2–13.0) and platelet count (OR = 0.78, 95% CI = 0.68–0.89) were independently associated with the presence of advanced fibrosis (F3–4). Further, LF index was independently associated with the presence of minimal fibrosis (F0–1) (OR = 0.25, 95% CI = 0.11–0.55). The area under the receiver–operator curve (AUROC) of LF index for predicting advanced fibrosis (0.84) was superior to platelets (0.82), FIB‐4 index (0.80) and aspartate aminotransferase/platelet ratio index (APRI) (0.76). AUROC of LF index (0.81) was superior to platelets (0.73), FIB‐4 index (0.79) and APRI (0.78) in predicting minimal fibrosis. Conclusion LF index calculated by RTE is useful for predicting liver fibrosis, and diagnostic accuracy of LF index is superior to serum fibrosis markers.